Incidence of Lung Cancer in Chronic Obstructive Pulmonary Disease Patients: Prognostic Factors and Survival Analysis - Niyomthong M.D, Parichat (Biomedical Sciences and Clinical Medicine, 2022)
OBJECTIVE To estimate the incidence of lung cancer in chronic obstructive pulmonary disease (COPD) patients, to identify the associated prognostic factors and to conduct a survival analysis. METHODS A retrospective cohort study was conducted between 1 June 2017 and 30 November 2020 with continued follow-up for an additional six months at the COPD Clinic of Phrae Hospital. Patients diagnosed with COPD and registered at the COPD Clinic who were age over 40 years and had a normal chest X-ray (CXR) within the previous year were enrolled. Patients diagnosed with or having a history of lung cancer, incomplete annual CXR or a follow-up period of less than six months were excluded. RESULTS A total of 316 COPD patients who met the inclusion criteria were analyzed. Seven COPD patients were newly diagnosed with lung cancer during the 3.5-year study period. The incidence rate of lung cancer in COPD patients was 0.69% per person-year. Smoking was a significant prognostic factor for lung cancer in the COPD patients. The mortality rate was significantly higher in patients with lung cancer. The mortality rate in COPD patients who developed lung cancer was 24.5% per person-year, higher than the 1.68% per personyear for patients who did not develop lung cancer. CONCLUSIONS The incidence rate of lung cancer in COPD patients is higher than in the general population and the mortality rate in COPD patients with lung cancer is higher than those without lung cancer. Annual CXR to detect lung cancer should be performed as part of routine lung cancer screening for COPD patients. Because CXR has lower sensitivity than low-dose computed tomography (LDCT) for detecting lung cancer in the early stage, this study found the incidence of lung cancer is slightly lower than previous reports that using LDCT. Moreover, CXR is simple to use, readily available and inexpensive.